Disinfection of Virtual Reality Devices in Health Care Settings: In Vitro Assessment and Survey Study - Scott C Roberts; Nancy L Havill; Rosa M Flores; Curtis Anthony Hendrix II; Maximillian J Williams; Richard S Feinn; Steven J Choi; Richard A Martinello; Asher M Marks; Thomas S Murray (JMIR Publications, 2022)
BackgroundVirtual reality (VR) devices are increasingly used in health care settings. The use among patients has the potential to unintentionally transmit pathogens between patients and hospital staff. No standard operating procedure for disinfection exists to ensure safe use between patients. ObjectiveThis study aims to determine the efficacy of disinfectants on VR devices in order to ensure safe use in health care settings. MethodsThree types of bacteria were inoculated onto porous and nonporous surfaces of 2 VR devices: the Meta Oculus Quest and Meta Oculus Quest 2. Disinfection was performed using either isopropyl alcohol or alcohol-free quaternary ammonium wipes. A quantitative culture was used to assess the adequacy of disinfection. A survey was separately sent out to VR device technicians at other pediatric health care institutes to compare the methods of disinfection and how they were established. ResultsBoth products achieved adequate disinfection of the treated surfaces; however, a greater log-kill was achieved on nonporous surfaces than on the porous surfaces. Alcohol performed better than quaternary ammonium on porous surfaces. The survey respondents reported a wide variability in disinfection processes with only 1 person reporting an established standard operating procedure. ConclusionsDisinfection can be achieved through the use of either isopropyl alcohol or quaternary ammonium products. Porous surfaces showed lesser log-kill rates than the nonporous surfaces, indicating that the use of an added barrier may be of benefit and should be a point of future research. Given the variability in the disinfection process across health care systems, a standard operating procedure is proposed.